Perbedaan Perkembangan Bayi Usia 0-6 Bulan yang Mendapatkan ASI Eksklusif dengan Susu Formula di Kecamatan Sampoiniet Kabupaten Aceh Jaya - Reda Ayini; Rotua Lenawati Tindaon; Rehmuliana Br Tarigan; Reliana Br Ginting; Renniafriana Hutasuhut; Dian Dian (Universitas Malahayati Lampung, 2023)
ABSTRACT The peak of children's growth and development occurs in the first 1000 days of human life, but the basic foundation in stimulating growth and development is in the age range of the first 0-6 months. Development is strongly influenced by nutrition. The development of babies with exclusive breastfeeding and formula milk will experience differences due to different nutritional content. The incidence of infants who received formula milk by 89.19% experienced developmental delays. Meanwhile, babies with exclusive breastfeeding of 67.57% experience normal development. The purpose of this study was to determine whether there were differences in the development of infants aged 0-6 months who received exclusive breastfeeding with formula milk in sampoiniet sub-district, Aceh Jaya Regency. The type of research used is observational analytical research with a Cross Sectional approach. . This research was conducted in September 2022 in Sampoinet District, Aceh Jaya Regency. The population in the study was babies aged 0- 6 months in Sampoinet District, Aceh Jaya Regency, which was 160 people. The sampling technique using Accidental sampling was 44 people. The results of this study used univariate and bivariate analysis with the Chi-Square test. Based on the Chi-square test, a P-value of 0.016 (0.05) was obtained, meaning that there were differences in the development of babies who were given exclusive breastfeeding and Formula Milk. The conclusion of this study is that there are differences in the development of babies who are given exclusive breastfeeding and Formula Milk. It is recommended for mothers to give exclusive breastfeeding to babies of 0-6 months, as it will adversely affect the development of the baby. Keywords: Exclusive Breastfeeding, Formula Milk, Baby Development. ABSTRAK Puncak tumbuh kembang anak terjadi pada 1000 hari pertama kehidupan manusia akan tetapi pondasi dasar dalam menstimulasi tumbuh kembang berada pada rentang usia 0-6 bulan pertama. Perkembangan sangat dipengaruhi oleh nutrisi. Perkembangan bayi dengan pemberian ASI Eksklusif dan susu formula akan mengalami perbedaan karena kandungan gizi yang berbeda. Angka kejadian bayi yang mendapatkan susu formula sebesar 89,19% mengalami keterlambatan perkembangan. Sedangkan bayi dengan ASI eksklusif sebesar 67,57% mengalami perkembangan normal. Tujuan penelitian ini untuk mengetahui apakah ada perbedaan perkembangan bayi usia 0– 6 bulan Yang mendapatkan asi eksklusif dengan Susu formula di kecamatan sampoiniet Kabupaten Aceh Jaya. Jenis penelitian yang digunakan adalah penelitian analitik observasional dengan pendekatan Cross Sectional. Penelitian ini dilakukan pada bulan September 2022 di Kecamatan Sampoinet Kabupaten Aceh Jaya. Populasi pada penelitian adalah bayi usia 0-6 bulan yang ada di Kecamatan Sampoinet Kabupaten Aceh Jaya yaitu sebanyak 160 orang. Teknik pengambilan sampel menggunakan Accidental sampling yaitu sebanyak 44 orang. Hasil penelitian ini menggunakan analisis univariat dan bivariat dengan uji Chi-Square. Berdasarkan uji Chi-square didapatkan nilai P-value 0,016 (0,05), berarti terdapat perbedaan perkembangan bayi yang diberikan ASI Eksklusif dan Susu Formula. Kesimpulan penelitian ini yaitu terdapat perbedaan perkembangan bayi yang diberikan ASI Eksklusif dan Susu Formula. Disarankan untuk ibu memberikan ASI Eksklusif pada bayi 0-6 bulan, karena akan mempengaruhi perkembangan bayi. Kata Kunci: ASI Eksklusif, Susu Formula, Perkembangan bayi